Визначення вологовмісту трансформаторного масла оптичними методами - Лобода, О. І. (Energy and Automation, 2017)
UDC 621.313 DETERMINATION OF MOISTURE CONTENT OF TRANSFORMER OIL BY OPTICAL METHODS A. Loboda The value of moisture is one of the important criteria of quality transformer oil and the criterion to determine the causes of deterioration of the dielectric properties of both the transformer was (TM) and solid isolation transformers. Therefore, an important issue is the analysis of existing methods for the quantitative determination of moisture content in TM. The purpose of research - setting moisture on the optical properties of cobalt dichloride. Materials and methods of research. The appearance of water in oil is a harbinger of accelerating failure of the power transformer and practice indicates inadequate supervision of electrical equipment or the aging of oil. To determine the moisture content of transformer oil, the following methods: hidrodkaltsiyevyy method; Karl Fischer titration; gas chromatography; mass spectrometry; Photo-acoustic spectroscopy, etc. Each of these methods has its advantages and disadvantages. Results. Dihloryd cobalt - one of the most widely used optical sensors water. To test the sensitivity of the optical sensor of high quality experiment added anhydrous СоС12 in transformer oil is fresh and analyzed changes in the absorption spectra in visible and UV - ranges. The absorption spectra of UV and visible range recorded at room temperature in the cell thickness of 10 mm spectrophotometer SF-46 in wavelength 190 ... 1100 nm at 600 nm / min at 1.0 nm slit width. The provisions of the lines in the spectra is given with an accuracy of ± 2,5 nm. Found that a sharp change in absorbance near wavelength 400 nm is due to absorption and scattering radiation structural inhomogeneities (colloidal, micellar solid particles) in transformer oil. Dissolve powder in oil СоС12 increases the optical density at a wavelength in the range of 360 ... 490 nm, and an increase in moisture content increases the intensity of the absorption band. However, the results suggest that optical method for determining the moisture content using СоС12 TM has a very high sensitivity and very promising for solving power energy. Conclusions The analysis of existing methods for determining the moisture content of transformer oil, offered the use of an optical method based on the dependence of the optical properties of cobalt dichloride moisture. The high sensitivity of the proposed method and the possibility of practical use.